Lived Experience of Iranian Family Caregivers of Tubercular Patients: A Qualitative Study - Mohebbi, Zinat; Dehbozorgi, Raziye; Setoodeh, Giti; Momennasab, Marzieh; Heydari, Naval; Shaygan, Maryam (Investigación y Educación en Enfermería, 2023)
Objective. To investigate the lived experience of family caregivers of persons with tuberculosis. Methods. In this study, the method of hermeneutic phenomenology. Data were collected through online in-depth semi-structured interviews with nine family caregivers of TB patients. The obtained data were thematically analyzed to explain the concept of home care for TB patients through van Manen's 6-step methodology. Results. After the thematic analysis, three main themes of caregivers'; mental distresses, quality care stasis, and facilitated care were obtained from 944 primary codes and 11 categories. Conclusion. Family caregivers of these patients suffer from mental distress. This issue affects the quality and ease of caregiving for these patients. Therefore, policymakers of this area should pay attention to the family caregivers of these patients and attempt to provide support; they should try to improve their quality of life.